Curcumin Regulates Cancer Progression: Focus on ncRNAs and Molecular Signaling Pathways - Wang, Haijun; Zhang, Ke; Liu, Jia; Yang, Jie; Tian, Yidan; Yang, Chen; Li, Yushan; Shao, Minglong; Su, Wei; Song, Na (Frontiers in Oncology, 2021)
Curcumin [(1E,6E) 1,7 bis(4 hydroxy 3 methoxyphenyl) hepta 1,6 diene 3,5 dione] is a natural polyphenol derived from the rhizome of the turmeric plant Curcuma longa. Accumulated evidences have presented curcumin’s function in terms of anti-inflammatory, antioxidant properties, and especially anti-tumor activities. Studies demonstrated that curcumin could exert anti-tumor activity via multiple biological signaling pathways, such as PI3K/Akt, JAK/STAT, MAPK, Wnt/β-catenin, p53, NF-ĸB and apoptosis related signaling pathways. Moreover, Curcumin can inhibit tumor proliferation, angiogenesis, epithelial-mesenchymal transition (EMT), invasion and metastasis by regulating tumor related non-coding RNA (ncRNA) expression. In this review, we summarized the roles of curcumin in regulating signaling pathways and ncRNAs in different kinds of cancers. We also discussed the regulatory effect of curcumin through inhibiting carcinogenic miRNA and up regulating tumor suppressive miRNA. Furthermore, we aim to illustrate the cross regulatory relationship between ncRNA and signaling pathways, further to get a better understanding of the anti-tumor mechanism of curcumin, thus lay a theoretical foundation for the clinical application of curcumin in the future.